Identification of polymorphisms in ELF5 and BMP2 genes and their impact on milk production in Brown Swiss cattle - Sönmez, Z; Özdemir, M (Journal of the Hellenic Veterinary Medical Society, 2025)
Identifying new genetic markers to comprehend the population structure and genetic foundation of cattle breeds, enhancing production and elevating yield quality, is vital in the realm of modern breeding technology. The aim of this study was to determine the genetic variations in E74-Like Factor 5 (ELF5), also known as Epithelial Specific ETS Factor 5, and Bone Morphogenetic Protein 2 (BMP2), also known as Bone Mineral Density Protein 2, and to correlate them with milk yield.es. The study’s purpose was to define new genetic markers in genes affecting milk yield performances in cattle. We used DNA samples from 90 animals of Brown Swiss cattle. Sequence analyses were applied to samples randomly selected after High-Resolution Melting analysis (HRMA), and polymorphic regions were identified. As a result of DNA sequences i) g.65825499 G/A transitions were determined for the intron 2 region of the ELF5 gene, ii) 5 different polymorphic regionsg.65826062 G/A, g.65825909 T/C, g.65826134 C/T, g.65826123 A/C and g. 65826138 T/C were identified for the exon 5 region of the ELF5 gene; iii) g.49551405 G/T, g.49551337 G/A, g.49551433 A/C, g.49551428 G/C and g.49551449 T/G polymorphic regions were identified for the exon 3 region of the Morphogenetic Protein 2 (BMP2) gene. There was no relationship between the polymorphic regions in the exon 5 and the intron 2 region of ELF5 and BMP2 gene polymorphic SNP polymorphisms and milk yield (P>0.05). Our results suggest that the newly identified polymorphisms in these genes can be used as molecular markers in modern breeding for defining various traits such as milk and growth yields. Keywords: ELF5, BMP2, SNP, milk yield, DNA sequencing.